Pemilihan Instruktur Kursus Menjahit Dari Alumni Lembaga Kursus Menjahit Kariahen dengan Sistem Pendukung Keputusan Tahani Method - Waruwu, Siyusuf (TIN: Terapan Informatika Nusantara, 2021)
The system of supporting decisions in which the results give the results in the selection of alumni institutions of the institution of keriahen Sewing Street Institution is the criteria of choice that can be the final decision in this case. In this case, Keriahen Sewing Road Institute provides an opportunity for alumni at the Keriahen Sewing Sewing Institute to be the place to be presented by the Keriahen Fine Sewing Institute. In this case the research is where else and the energy or energy or energy that banyan and skill. This decision is in order to work style the institution on the institution sew keriahen in this research the author of the support system so the main goal is to easily lead the Keriahen Sewing Education Institute in selecting educational institutions sewing education. The results of this study provide great benefits at the leadership of Keriahen Sewing Road Institute to continue sewing business efforts in the future